Do local land institutions make a dime’s worth of a difference in rural land markets?: evidence from Malawi - Matchaya, Greenwell C. (Emerald Publishing Limited, 2014)
Purpose: It has been argued that traditional land transfer systems provide disincentives for farmers to trade their land, thus reducing land availability and depressing productivity. The paper investigates the determinants of land rentals under customary land ownership in matri- and patrilineal traditions and under formal land registration in the rural areas of Malawi. Design/methodology/approach: Using new data collected from around 100 households farming around 200 parcels in three regions of Malawi, a number of models are estimated with ordinary least squares (OLS). Findings: The paper finds some evidence that some variables within the traditional system of land holding are crucial for land rentals. However, when land titles are used as a proxy for security of tenure, none of the relationships commonly hypothesised between land ownership security and land lease are corroborated. Land registration is found to have no significant effects on land and rentals. Originality/value: The uniqueness of this paper rests in it its use of context specific constructs of land ownership security. Moreover the tested hypotheses emerge from a theoretical model that is unique to the literature on rural land markets and land tenure.